Quantifying Exciton Annihilation Effects in Thermally Activated Delayed Fluorescence Materials. Issue 3 (6th December 2021) - Thakur, Kalyani; van der Zee, Bas; Wetzelaer, Gert‐Jan A. H.; Ramanan, Charusheela; Blom, Paul W. M
Abstract: Important parameters for the design and performance of thermally activated delayed fluorescence (TADF) emitters are the forward and reverse intersystem crossing rates between singlet and triplet states. The magnitude of these rates is determined from the prompt and delayed transient photoluminescence decay. It is demonstrated that this photoluminescence decay strongly depends on the initial photoexcited population density due to exciton–exciton annihilation processes. By kinetic modeling of the power‐dependent time‐resolved photoluminescence of the TADF emitter 9, 10‐bis(4‐(9H‐carbazol‐9‐yl)‐2, 6‐dimethylphenyl)‐9, 10‐diboraanthracene (CzDBA), singlet–triplet annihilation and triplet–triplet annihilation are identified as the main loss processes with rate constants in the order of 10 −17 m 3 s −1 . Neglecting these quenching processes leads to erroneous estimates of the (reverse) intersystem crossing rates. Abstract : Accurate kinetic modeling of the photoluminescence (PL) decay of a thermally activated delayed fluorescence (TADF) emitter is important to extract intrinsic parameters like the(reverse) intersystem crossing rate. Here, the PL decay of the TADF emitter 9, 10‐bis(4‐(9H‐carbazol‐9‐yl)‐2, 6‐dimethylphenyl)‐9, 10‐diboraanthracene is modeled, taking annihilation processes into account. The authors find that triplet–triplet annihilation and singlet–triplet annihilation are the dominant exciton annihilation processes.